Estudo da mutação c.1080+1G>T do gene P3H1 em pacientes com osteogênese imperfeita atendidos no Estado do Espírito Santo, Brasil - Santos, Mário Sérgio Ribeiro dos (2019)
Osteogenesis imperfecta (OI) is a rare inherited bone disease characterized by fragile and brittle bones that results in fractures in children and adults. It is a disorder related to collagen, the main component of the extracellular matrix of connective tissues. In recent years, many genes have been identified with different inheritance patterns related to OI. These anomalies are commonly related to the mutations in genes encoding type I collagen, responsible for the appearance of the dominant autosomal forms of the disease. Among those inherited in an autosomal recessive form stands out the P3H1 gene, the encoder of one of the three protein components forming the 3- hydroxylation complex of proline of collagen type I. This work aimed to study the c.1080+1G>T mutation of the gene P3H1 in patients with clinical diagnosis of OI in the state of Espírito Santo (ES), Brazil. Sanger Sequencing was performed in 10 patients attended at reference hospitals in the treatment of OI in the ES state. The c.1080+1G>T mutation of the gene P3H1 was not identified in any patient studied in this study. Despite the small sample size of this research, the results of this work suggest that this mutation is rare in patients with ES. Characterizing the distribution of mutations in genes related to OI increases our knowledge about the genetic and phenotypic variability present in the disease in different populations and helps in the planning of new strategies for molecular diagnoses of OI.